Qualidade analítica baseada no projeto como ferramenta de desenvolvimento de métodos em cromatografia líquida de ultra eficiência - Solon, Lilian Grace da Silva (2016)
The pharmaceutical industry and analytical laboratories around the world have focused on quality, safety and efficacy of their products. Processes used to minimize risks, such as Quality by Design (QbD), which recently has been attributed to the development of analytical methods, especially chromatographic methods. The Analytical Quality by Design (aQbD) uses planning tools experiments, risk analysis and continuous monitoring. For this, it makes use of simulation software, statistical tools and chemometrics. It is known that chromatographic methods are well consolidated and required by the regulatory agencies. It has been applied in various determinations in the pharmaceutical field, such as identification and quantification of drugs, metabolites, degradation products and impurities. The aim of this study was to use aQbD tools for the development of methods for ultra high performance liquid chromatography (UHPLC). Four methods were developed, namely: simultaneous quantification of dexamethasone acetate and clotrimazole in semisolid dosage forms, via HPLC to UHPLC method transfer (Chapter 1); simultaneous determination of corticosteroids and preservatives in solid core column with particle size of 1.3 μm by using simulation software (Chapter 2); betamethasone valerate quantification in samples of cream, gel, lotion and ointment after method development by full factorial design 33 (Chapter 3); and simultaneous determination of corticosteroids after retention factor prediction model by QSRR (Chapter 4). The results showed that despite the need for optimization by the analyst, the use of aQbD tools such as statistical design or use of software, the aQbD is promising in the development of chromatographic methods of ultra efficiency, since they were able to promote time savings, lower costs and risks. The tests showed satisfactory results in terms of analysis speed and decrease of solvent consumption.